EKONOMI MATEMATIKA: BAGAIMANA FUNGSI LINEAR MENENTUKAN KESIMBANGAN HARGA PASAR - Rusmariani, Yuly (JENTRE, 2023)
The primary objective of this scientific inquiry is to thoroughly investigate and expound upon the practical application and implementation of linear function equations within the domain of economic mathematics. The central focus lies in dissecting the intricate modeling of market equilibrium prices, with a specific emphasis on the assessment of consumer and producer surpluses associated with essential commodities, such as rice. The core methodology of this study involves an in-depth literature review, which serves as the backbone for understanding the nuances of market equilibrium price models and the nuanced application of linear equations within economic mathematics. The economic and business disciplines are often considered semi-precise sciences, demanding a nuanced blend of qualitative and quantitative analyses to achieve a comprehensive understanding of their multifaceted dynamics. In this context, quantitative analysis in economics and business invariably necessitates the utilization of mathematics as an indispensable tool. Hence, this study consciously adopts a quantitative research approach, a methodological process rooted in the systematic acquisition of knowledge using numerical data as a tool to dissect and analyze crucial information relevant to the subject matter. Delving into the intricacies of supply and demand laws through the lens of linear functions, the study ultimately concludes that the adoption of mathematical models grounded in linear functions holds the potential to effectively determine the demand and supply functions, especially concerning staple commodities like rice. Moreover, it proves instrumental in identifying and comprehending market equilibrium, furnishing invaluable insights that can significantly contribute to a nuanced understanding and effective management of economic phenomena. In essence, this research aims not only to contribute to the theoretical discourse in economic mathematics but also to provide practical insights that can inform decision-making processes within the realms of economics and business.